Genome and Transcriptome Sequencing Analysis of Fusarium commune Provides Insights into the Pathogenic Mechanisms of the Lotus Rhizome Rot - Weigang Kuang; Lianhu Zhang; Lifang Ye; Jian Ma; Xugen Shi; Yachun Lin; Xiaotang Sun; Ruqiang Cui (Microbiology Spectrum, 2022)
ABSTRACT Fusarium wilt, a vascular wilt caused by F. commune, has been a serious problem for the lotus. Although some F. commune isolate genomes have been sequenced, little is known about the genomic information of the strain that causes Fusarium wilt of aquatic plants. In this study, the genome of F. commune FCN23 isolated from lotuses in China was sequenced using Illumina and PacBio sequencing platforms. The FCN23 genome consisted of 53 scaffolds with a combined size of 46,211,149 bp. According to the reference genome, F. oxysporum f. sp. lycopersici 4287 isolated from tomato, it was finally assembled into 14 putative chromosomes, including 10 core and 4 lineage-specific chromosomes. The genome contains about 3.45% repeats and encodes 14,698 putative protein-coding genes. Among these, 1,038 and 296 proteins were potentially secreted proteins and candidate effector proteins, respectively. Comparative genomic analysis showed that the CAZyme-coding genes and secondary metabolite biosynthesis genes of FCN23 were similar to those of other Ascomycetes. Additionally, the transcriptome of FCN23 during infection of lotus was analyzed and 7,013 differentially expressed genes were identified. Eight putative effectors that were upregulated in the infection stage were cloned. Among them, F23a002499 exhibited strong hypersensitive response after transiently expressed in Nicotiana benthamiana leaves. Our results provide a valuable genetic basis for understanding the molecular mechanism of the interaction between F. commune and aquatic plants. IMPORTANCE Fusarium commune is an important soilborne pathogen with a wide range of hosts and can cause Fusarium wilt of land plants. However, there are few studies on Fusarium wilt of aquatic plants. Lotus rhizome rot mainly caused by F. commune is a devastating disease that causes extensive yield and quality losses in China. Here, we obtained high-quality genomic information of the FCN23 using Illumina NovaSeq and the third-generation sequencing technology PacBio Sequel II. Compared to the reference genome F. oxysporum f. sp. lycopersici strain 4287, it contains 11 core and 3 lineage-specific chromosomes. Many differentially expressed genes associated with pathogenicity were identified by RNA sequencing. The genome and transcriptome sequences of FCN23 will provide important genomic information and insights into the infection mechanisms of F. commune on aquatic plants.